2018
DOI: 10.1111/jssr.12576
|View full text |Cite
|
Sign up to set email alerts
|

Scriptural Coping: An Empirical Test of Hermeneutic Theory

Abstract: This study develops and tests a theory of scriptural coping. Using elements from hermeneutic theory as our guide, we contend that (1) specific life exigencies will increase the likelihood of someone turning to scripture for relevant insights and (2) reading scripture for relevant insights will moderate associations between exigencies and psychological well‐being. Analyzing nationally representative data from the 2012 General Social Survey (n = 1,551), we find that poor self‐rated health and low socioeconomic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 77 publications
(118 reference statements)
1
18
0
Order By: Relevance
“…Although the present study has advanced the nascent religion‐sleep literature, several issues remain unaddressed. First, additional religious domains should be explored in the future, including: (1) specific aspects of congregational support practices, including spiritual support (Krause ); (2) diverse styles and practices of prayer and scriptural study (DeAngelis et al ; Ellison et al. ; Poloma and Gallup ); (3) religious coping styles and practices (Ano and Vasconcelles ; Pargament ); and (4) religiously inspired character strengths or virtues, such as hope, gratitude, and forgiveness (Krause ; Krause and Ellison ; Krause et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the present study has advanced the nascent religion‐sleep literature, several issues remain unaddressed. First, additional religious domains should be explored in the future, including: (1) specific aspects of congregational support practices, including spiritual support (Krause ); (2) diverse styles and practices of prayer and scriptural study (DeAngelis et al ; Ellison et al. ; Poloma and Gallup ); (3) religious coping styles and practices (Ano and Vasconcelles ; Pargament ); and (4) religiously inspired character strengths or virtues, such as hope, gratitude, and forgiveness (Krause ; Krause and Ellison ; Krause et al.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, although our religious items are adequate for gauging key constructs in our study, single‐item religion measures can still suffer from low reliability. The development of multi‐item measures of scripture reading or afterlife beliefs, for instance, would be a welcome addition to work in this field (e.g., DeAngelis, Bartkowski, and Xu ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is consistent with Hypothesis 2. Although no previous research has examined the relationship between Christian talk radio and IPV-or marital quality in general-this finding is expected in light of the research by Doss et al (2009) that couples facing relationship challenges sought help by reading books and of the study by DeAngelis et al (2018) that showed individuals use the reading of scripture as a help-seeking behavior. Listening to talk radio should be an even more likely target of help-seeking in light of the findings by Rubin (2000) that talk radio listeners often consider a host to be not only a relational partner but also a credible source of information.…”
Section: Intimate Partner Violencementioning
confidence: 96%
“…Based on their recent study, DeAngelis et al (2018) observed that "readers approach scripture with preconceived biases conditioned by life experiences and other social constraints" (p. 12). Thus, people will turn to scripture for a variety of reasons and with varied perspectives based, in part, on their own needs.…”
Section: Introductionmentioning
confidence: 99%